Using recoverable sulfurized magnetic biochar for active capping to remediate multiple heavy metal contaminated sediment. (1st January 2023) - Hsu, Che-Jung; Cheng, Yung-Hua; Chung, Adrienne; Huang, Ying-Pin; Ting, Yu; Hsi, Hsing-Cheng
Abstract: Due to anthropogenic activities, heavy metals are discharged into the hydrosphere and deposit onto the sediment. Heavy metals remobilize through physical disturbance and change in environmental conditions, posing a risk to environments and human health. Among several remediation methods, active layer capping is considered to be more feasible due to its financial and technical advantages; however, its long-term effects remain unknown. To overcome this problem, this work applied a novel, recoverable amendment, sulfurized magnetic biochar (SMBC), to remediate multiple heavy metal (Cu, Ni, Zn, Cr, Hg, and MeHg) contaminated sediment. Physiochemical characterization shows magnetite (Fe3 O4 ) crystalline in both magnetic biochar (MBC) and SMBC, with such characteristics resulting in a greater surface area (324.9 and 346.3 m 2 /g) than BC (39.6 m 2 /g) and SBC (65.0 m 2 /g). FeS crystalline was also observed in SMBC, which plays an important role in controlling heavy metal release from sediment. Microcosm experiments indicated the effectiveness of SMBC in lowering aquatic Cu, Ni, Zn, Hg, and MeHg releases was significantly greater than the other three biochar materials. Notably, the recovery of SMBC by magnetism was 87%, demonstrating the exceptional recoverability of SMBC from seawater and sediment. Based on its robust capability in lowering Cu, Ni, Zn, Hg, and MeHg release and excellent recoverability from seawater and sediment, this technique represents a practical alternative to conventional approaches for heavy metal immobilization from sediment. Graphical abstract: Image 1 Highlights: Sulfurized magnetic biochar (SMBC) was used to remediate metal-containing sediment. SMBC had high surface area (346.3 m 2 /g) and micropore surface area (297.2 m 2 /g). SMBC effectively immobilized the most heavy metals (Cu, Ni, Zn, Hg, and MeHg). FeS in SMBC plays an important role in controlling heavy metal release. SMBC was successfully recovered via magnetic separation.